Are calcium channel blockers effective for treating primary Raynaud's phenomenon?. Issue 8 (August 2017) - Miller, Deborah E.; Oshman, Lauren
Abstract : EVIDENCE‐BASED ANSWER : As a drug class, calcium channel blockers (CCBs) are minimally effective for reducing the frequency of attacks of primary Raynaud's phenomenon (SOR: A, metaanalysis of RCTs) and reducing the severity of attacks by about 14% (SOR: B, meta‐analysis of heterogenous RCTs). Nifedipine may be more effective than other agents in this class (SOR: B, consistent subanalyses within systematic reviews).